Reforms and revenue mobilization in Africa: Are semi-autonomous revenue authorities (SARAs) effective? - (:unkn) unknown (My University, 2019)
We study effect of semi-autonomous revenue administration reform on tax revenues in sub-Saharan Africa. From a set of data collected on 40 countries between 1980 and 2010, we find a diversified effect on total non-resource tax revenue. In medium term, semi-autonomous revenue authorities don't collect more revenue than traditional administrations and their efficiency diminishes over time. The main conclusion is that semi-autonomous revenue administrations are not a panacea for improving revenue mobilization in Sub-Saharan African countries.
Keywords: African Research